Effects of the clathrin inhibitor Pitstop-2 on synaptic vesicle recycling at a central synapse in vivo - Paksoy, Alp; Hoppe, Simone; Dörflinger, Yvette; Horstmann, Heinz; Sätzler, Kurt; Körber, Christoph (Frontiers in Synaptic Neuroscience, 2022)
Four modes of endocytosis and subsequent synaptic vesicle (SV) recycling have been described at the presynapse to ensure the availability of SVs for synaptic release. However, it is unclear to what extend these modes operate under physiological activity patterns in vivo. The coat protein clathrin can regenerate SVs either directly from the plasma membrane (PM) via clathrin-mediated endocytosis (CME), or indirectly from synaptic endosomes by SV budding. Here, we examined the role of clathrin in SV recycling under physiological conditions by applying the clathrin inhibitor Pitstop-2 to the calyx of Held, a synapse optimized for high frequency synaptic transmission in the auditory brainstem, in vivo. The effects of clathrin-inhibition on SV recycling were investigated by serial sectioning scanning electron microscopy (S3EM) and 3D reconstructions of endocytic structures labeled by the endocytosis marker horseradish peroxidase (HRP). We observed large endosomal compartments as well as HRP-filled, black SVs (bSVs) that have been recently recycled. The application of Pitstop-2 led to reduced bSV but not large endosome density, increased volumes of large endosomes and shifts in the localization of both types of endocytic compartments within the synapse. These changes after perturbation of clathrin function suggest that clathrin plays a role in SV recycling from both, the PM and large endosomes, under physiological activity patterns, in vivo.